Hydrogen production by steam reforming of ethanol over copper doped Ni/CeO_2 catalysts - 刘其海 刘自力 周新华 李翠金 丁娇 (Journal of rare earths, 2011)
High surface area CeO2 was prepared by the surfactant-assisted route and was employed as catalyst support. The 0-3 at.% Cu doped Cu-Ni/CeO2 catalysts with 10 wt.% and 15 wt.% of total metal loading were prepared by an impregnation-coprecipitation method. The influence of Cu atomic content on the catalytic performance was investigated on the steam reforming of ethanol （SRE） for H2 production and the catalysts were characterized by N2 adsorption, inductively coupled plasma （ICP）, X-ray diffraction （XRD）, transmission electron microscopy （TEM）, temperature-programmed rerduction （TPR） and H2-pulse chemisorption techniques. The activity and products distribution behaviors of the catalysts were significantly affected by the doped Cu molar content based on the promotion effect on the dispersion of NiO particles and the interactions between Cu-Ni metal and CeO2 support. Significant increase in the ethanol conversion and hydrogen selectivity were obtained when moderate Cu metal was doped into the Ni/CeO2 catalyst. Over both of the 10Ni98.5Cu1.5/CeO2 and 15Ni98.5Cu1.5/CeO2 catalysts, more than 80% of ethanol conversion and 60% of H2 selectivity were obtained in the ethanol steam-reforming when the reaction temperature was above 450 ℃.